Periodically repeating fast radio bursts: Lense–Thirring precession of a debris disk?. (29th June 2020) - Chen, Wen-Cong
Abstract: Recently, repeating fast radio bursts (FRBs) with a period of P FRB = 16.35 ± 0.18 d from FRB 180916.J0158+65 were reported. It still remains controversial how such a periodicity might arise for this FRB. In this Letter, based on an assumption of a young pulsar surrounding by a debris disk, we attempt to diagnose whether Lense–Thirring precession of the disk on the emitter can produce the observed periodicity. Our calculations indicate that the Lense–Thirring effect of a tilted disk can result in a precession period of 16 d for a mass inflow rate of 0.5–1.5 × 10 18 g s −1, a pulsar spin period of 1–20 ms, and an extremely low viscous parameter α = 10 −8 in the disk. The disk mass and the magnetic field of the pulsar are also constrained to be ∼10 −3 M ⊙ and <2.5 × 10 13 G. In our model, a new-born pulsar with normal magnetic field and millisecond period would successively experience the accretion and propeller phases, and is visible as a strong radio source in the current stage. The rotational energy of such a young neutron star can provide the observed radio bursting luminosity for 400 yr.